1992
DOI: 10.1210/jcem.74.3.1311000
|View full text |Cite
|
Sign up to set email alerts
|

Adrenal incidentaloma and patients with homozygous or heterozygous congenital adrenal hyperplasia.

Abstract: Adrenal tumors are being detected more frequently in consequence of the wider application of increasingly sensitive radiological investigation techniques. According to the working hypothesis that more silent adenomas could develop from hyperplastic tissue areas under increased stimulation of the adrenal cortex, heterozygous and homozygous patients with congenital adrenal hyperplasia (CAH) were studied. A high incidence of adrenal masses, nearly 82% in homozygous and 45% in heterozygous patients, was found. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
117
3
10

Year Published

1993
1993
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(132 citation statements)
references
References 8 publications
2
117
3
10
Order By: Relevance
“…In congenital adrenal hyperplasia, adrenal size correlated with patients' age and the age at which therapy was started (47). On the other hand, no correlation between tumor size and serum 17-hydroxyprogesterone concentration was found in these patients, at variance with findings of a relationship between tumor size and 17-hydroxyprogesterone-stimulated secretion reported in patients with adrenal incidentalomas not associated with congenital adrenal hyperplasia (48 -50).…”
Section: Congenital Adrenal Hyperplasiamentioning
confidence: 61%
See 1 more Smart Citation
“…In congenital adrenal hyperplasia, adrenal size correlated with patients' age and the age at which therapy was started (47). On the other hand, no correlation between tumor size and serum 17-hydroxyprogesterone concentration was found in these patients, at variance with findings of a relationship between tumor size and 17-hydroxyprogesterone-stimulated secretion reported in patients with adrenal incidentalomas not associated with congenital adrenal hyperplasia (48 -50).…”
Section: Congenital Adrenal Hyperplasiamentioning
confidence: 61%
“…In congenital adrenal hyperplasia, decreased production of cortisol leads to increased adrenocorticotropin secretion, resulting in adrenal hyperplasia. Jaresh et al (47) reported a high prevalence of adrenal masses, nearly 82% in homozygous and 45% in heterozygous patients with congenital adrenal hyperplasia, including deficiencies of 21-hydroxylase, 11b-hydroxylase, and 3b-hydroxysteroid dehydrogenase.…”
Section: Congenital Adrenal Hyperplasiamentioning
confidence: 99%
“…The latter observations led to the proposal that undiagnosed mild forms of congenital 21-hydroxylase deficiency or a heterozygous state for this disorder, which results in decreased cortisol secretion and consequently increased ACTH secretion, may be a predisposing factor for the development of incidental adrenocortical tumors. Consistent with this concept, one study showed that adrenocortical adenomas may be present in 82% of homozygous patients as well as in 45% of heterozygous carriers for congenital 21-hydroxylase deficiency (23).…”
Section: Introductionmentioning
confidence: 75%
“…Since osteopenia and osteoporosis are rare in pediatric CAH patients, routine evaluation of bone mineral density is discouraged in children, but should be considered in any patient who has been subjected to chronic high doses of glucocorticoids or who has sustained fractures (2 | ⊕OOO). Adrenal nodules have been identified more frequently in CAH patients and carriers than in the general population [15], however, adrenal imaging (generally CT scans) ought to be reserved for those patients who have an atypical clinical or biochemical course due to the high radiation burden of frequent screening (2 | ⊕OOO). Males with classic CAH should be periodically screened with ultrasound for testicular adrenal rests [16].…”
Section: Complications Of Cahmentioning
confidence: 99%